Blade technology from the Pampas Valley, Ayacucho, Peru (ca. 0-900 A.D) - Yataco Capcha, Juan José (2021)
A labor research of a lithic series from two archaeological sites located at the Chusqui District (Ayacucho) revealed the occurrence of true blades of basalt and quartz sandstone that were associated with sherds of both Early Intermediate Pe-riod and the Middle Horizon (ca. 0-900 AD). In this report we present the results of the examination of this series by stressing out some key and relevant data like the preparation of the blade cores from which blades were removed as well as the skills of the flintknappers applying this kind of rare recorded lithic technology yet not for that reason less important.